Pelatihan Pengembangan Bahan Ajar Berbasis Etnopedagogi untuk Meningkatkan Literasi Numerasi bagi Guru SD - Alimuddin, Nurkhaerat; Nurwahidah, Nurwahidah; Yeni Suranti, Ni Made; Fauzi, Asri; Ibrahim, Ibrahim (State Islamic University of Mataram, 2025)
The purpose of this community service activity is to improve teacher competency in developing relevant ethnopedagogy-based teaching materials and supporting the strengthening of elementary school students' literacy and numeracy. This community service is motivated by the need for teachers to have training in preparing contextual teaching materials that support the learning process. The activity was carried out at SDN 27 Cakranegara with the involvement of the principal, teachers, and a team of lecturers. The implementation method consisted of socialization, training, technology application, evaluation, and the program's ongoing phase. The results of the community service implementation showed an increase in teachers' understanding of the concepts of literacy, numeracy, and ethnopedagogy as well as an increase in teachers' skills in producing creative, contextual, and culturally appropriate teaching modules. The response results showed a very high participant satisfaction index and reflected the optimal achievement of the training objectives.